Cultural Knowledge Management for Sustainable Tourism - Pengmol, Taptim (Journal of Local Governance and Innovation, 2019)
This article discusses the cultural knowledge management for sustainable tourism as a fundamental body knowledge of cultural knowledge construction and transmission which exhibits a human group’s prosperity and growth. The goals of this study were to examine, accumulate, and propose the cultural knowledge management for sustainable tourism. This study covers the following areas of study: the culture, sustainable tourism, knowledge management, and cultural knowledge management for sustainable tourism. By using SECI Model (Nonaka and Takeuchi, 1995) and Frost’s Theory (2010) for data analysis, the study found the seven-step cultural knowledge management process as follows: 1) Identification of Needs, 2) Externalization 3) Acquisition, Creation or Elimination of Knowledge 4) Combination 5) Storing Knowledge 6) Retrieval, Application, and Sharing Knowledge and 7) Internalization. The process repeats itself to develop the knowledge management for cultural sustainability.